Landmark based shape variation of normal male, female and sex-reversed tilapia (Oreochromis niloticus) in Bangladesh (Progressive Agriculture, 2015)
The truss network systems constructed with the help of landmark were evaluated to infer the shape of normal male, female and monosex male tilapia. A total of sixty (60) individuals from different sources (Subarna Agro Based Initiative and BismillahAgro Production) were collected during September-December, 2013. All the data of the studied characteristics were obtained using the digital photograph of the samples which were analyzed through professional image measurement software. Nine morphometric and eight meristic characters were considered along with twenty six truss network measurements. Highly significant difference (P